MONOPOLES AND GEODESICS - Hitchin, N (Springer-Verlag, 1982)
Using the holomorphic geometry of the space of straight lines in Euclidean 3-space, it is shown that every static monopole of charge k may be constructed canonically from an algebraic curve by means of the Atiyah-Ward Ansatz Mathematical expression. © 1982 Springer-Verlag.